Computational Modeling of Primary Blast Lung Injury: Implications for Ventilator Management. (21st March 2019) - Herrmann, Jacob; Tawhai, Merryn H; Kaczka, David W
Abstract: Primary blast lung injury (PBLI) caused by exposure to high-intensity pressure waves is associated with parenchymal tissue injury and severe ventilation-perfusion mismatch. Although supportive ventilation is often required in patients with PBLI, maldistribution of gas flow in mechanically heterogeneous lungs may lead to further injury due to increased parenchymal strain and strain rate, which are difficult to predict in vivo . In this study, we developed a computational lung model with mechanical properties consistent with healthy and PBLI conditions. PBLI conditions were simulated with bilateral derecruitment and increased perihilar tissue stiffness. As a result of these tissue abnormalities, airway flow was heterogeneously distributed in the model under PBLI conditions, during both conventional mechanical ventilation (CMV) and high-frequency oscillatory ventilation. PBLI conditions resulted in over three-fold higher parenchymal strains compared to the healthy condition during CMV, with flow distributed according to regional tissue stiffness. During high-frequency oscillatory ventilation, flow distribution became increasingly heterogeneous and frequency-dependent. We conclude that the distribution and rate of parenchymal distension during mechanical ventilation depend on PBLI severity as well as ventilatory modality. These simulations may allow realistic assessment of the risks associated with ventilator-induced lung injury following PBLI, and facilitate the development of alternative lung-protective ventilation modalities.